Perilaku Bullying Pada Anak Di Taman Kanak-Kanak Aisyiyah Bustanul Athfal I Cabang Bara-Baraya Kota Makassar - Fadhilah Purnama; Herman Herman; Syamsuardi Saodi; Herman (Publikasi Pendidikan, 2018)
The objective of this reserach is to collect information about the bullying behavior of children in kindergarten Aisyiyah Bustanul Athfal I Bara-Baraya Branch of Makassar City. This research used qualitative approach and qualitative descriptive research. The subject of research is the child in Kindergarten Aisyiyah Bustanul Athfal I Bara-Baraya Branch of Makassar City in group B with the number of students 23. Data collections in this research are observation, interview and documentation. Results of research on Bullying Behavior in Children in Kindergarten Aisyiyah Bustanul Athfal I Bara-Baraya Branch of Makassar City shows there is bullying behavior in the form of bullying verbal and physical bullying. The number of dominant Bullying cases occurring is physical Bullying behavior of hitting, kicking, robbing, pushing, destroying, twisting arms, throwing and threatening compared to the number of cases of verbal Bullying behavior in the form of calling by other names and mocking. In terms of verbal bullying behavior is generally more experienced by girls than boys, while for physical bullying behavior experienced more by boys than girls. Then Performers in verbal and physical bullying behavior are generally done by boys compared to girls.